Changing Trends in the Epidemiology and Risk Factors of Pneumocystis Pneumonia in Spain - Pereira-Díaz, Estefanía; Moreno-Verdejo, Fidel; de la Horra, Carmen; Guerrero, José A.; Calderón, Enrique J.; Medrano, Francisco J. (Frontiers in Public Health, 2019)
Objective: The information about the epidemiology of Pneumocystis pneumonia (PcP) in Europe is scarce, and in Spain there are only data nationwide on patients with HIV infection. This study has been carried out with the aim of knowing in our country the current epidemiological spectrum and the risk factors of PcP. Methods: Observational, descriptive transversal study that included all patients admitted in Spain with diagnosis upon discharge of PcP registered in the National Health System’s Hospital Discharge Records Database of Spain, between 2008 and 2012. Results: A total of 4554 cases of PcP were recorded, 1204 (26.4%) in HIV-negative patients. During the study period, mean annual incidence (cases per million) was 19.4, remaining globally stable, increasing from 4.4 to 6.3 in patients without HIV infection and decreasing from 15.5 to 13.4 among HIV-infected patients. Risk factors were identified in 85.5% of HIV-negative cases, the most frequent being hematological malignancies (29%), chronic lung diseases (15.9%), and non-hematological neoplasm (14.9%). Mean mortality and hospitalization cost were high (25.5% and 12000 euros, respectively). Conclusions: The results of this first nationwide study in Spain allow a change in the misconception that, after the AIDS epidemic, PcP is an infrequent disease, showing that today it is an emerging problem in patients without HIV infection. These findings underlines the need for increased efforts towards a better characterization of risk groups to improve prophylactic strategies and reduce the burden of disease.